Lift Every Voice: Exploring the Stressors and Coping Mechanisms of Black College Women Attending Predominantly White Institutions. (January 2018) - Shahid, Naysha N.; Nelson, Tamara; Cardemil, Esteban V.
In the past 40 years, there has been a significant increase in Black students' enrollment at predominantly White institutions (PWIs). Meanwhile, research shows that Black students often experience difficulty with transitioning and adjusting to PWIs. Previous research has effectively documented the challenges facing a significant number of Black students at PWIs; however, less is known about the experiences of Black women in particular. This study examined stress from racial tension experienced among 129 Black undergraduate women at PWIs in the Northeast region of the United States, as well as the potential moderating factors of the theorized Strong Black Woman concept and the Africultural coping theory. Hierarchical regression analyses indicated a significant positive association between racial tension experienced on campus and stress. Results also indicated that only Africultural coping was a significant moderator of this relationship, such that there was a weaker relationship between racial tension and stress among the participants who engaged more in Africultural coping. Policy implications for improving the campus racial climate and the academic experiences of Black college women at PWIs are discussed.